Borneo Maternity Care - Ruslan, Rasyidah; Mohd Bantilan, Nurliana; Mataut, Jasonfressley; Saini, Mazuin; Jailih, Victor (2015)
The Borneo Maternity Care is our company that provides service to customer. The concept of business is to give care during confinement to mother and their babies. For example we give the confinement practice which is Malay traditional practices aimed at helping new mother recover from the rigours of pregnancy, labour and birth. We provide an abdomen massage and tummy blind with special postnatal corset and many more. The nature of our business is partnership. Our base office and business located at Kampung Minyak, Kudat. We expect to start up our business on 13 May 2015. With collaboration from Nursery Exotix Matahari, Pembekal Mama Ayah and Sunti Dara Company we have an opportunity to start a business regarding to care during confinement using traditional herbs. The future prospects of our business are people around Sabah and the same time aiming the one Malaysia. This is because based on the Birth Statistic by Kementerian Kesihatan Malaysia , the number of birth high. The demands for care confinement are also high. We also see women with professional carrier as a huge opportunity for our business. We expect our sales will increase on second and third year at 5% and 7% respectively.